Effects of salinity on the microscopic interaction and sedimentation behavior of halloysite nanotube - Kwon, Yeong Man; Noh, Namgyu; Dae, Kyun Seong; Qureshi, Yusra; Kwon, Ji Hwan; Cho, Gye Chun; Chang, Ilhan; Yuk, Jong Min (Applied Clay Science, 2024)
The response of clay minerals to changes in pore fluid salinity, particularly in coastal areas such as bays, lagoons, sounds, sloughs, and estuaries, has not been extensively studied. Herein, the influence of salinity exchange on the microscopic interaction and sedimentation behavior of halloysite nanotubes in an aqueous condition was investigated. In-situ microscopic observations and macro-scale sedimentation experiments reveal that halloysite nanotubes tend to disperse in pore fluids with high ionic strength because salt ions weaken the edge-to-face halloysite fabrics. Salinity exchange experiments demonstrate the permanent alteration of flocculation and sedimentation behavior due to the residual salt ions on the HNT surfaces. Even when the salt concentration is restored to its initial value, the presence of residual salts leads to the formation of a large and open floc structure, resulting in slower settling and a loosely packed final sediment. Our study provides a thorough understanding of the salt effect on sediment formation, including changes in the microscopic clay particle fabrics during salinity exchange.
Keywords: DLVO theory; Halloysite nanotube; Halloysite nanotubes; In-situ liquid-phase microscopy; Liquid Phase; Liquid phasis; Microscopic interaction; Residual salts; Salinity; Salt ions; DLVO theory; Flocculation; Halloysite nanotube (HNT); In-situ liquid-phase microscopy; Salinity; Sedimentation